2019
DOI: 10.1186/s12880-019-0394-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of tensile stress in carotid arteries of healthy human subjects with varying age

Abstract: BackgroundArterial remodeling is thought to reflect the adaptation of the vessel wall to mechanical and hemodynamic stimuli and contributes to the progression of cardiovascular and cerebrovascular diseases. Tensile stress (TS) is one of the mechanical properties of the artery wall. The purpose of this study was to investigate the tensile stress change (TS) of carotid artery with varying viscoelasticity in healthy subjects within two groups of different ages.MethodsForty-five subjects were recruited and randoml… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Mechanical stretching can cause structural alteration of the arterial wall, including hyperplasia and hypertrophy of vascular smooth muscles, leading to arterial remodeling. Carotid tensile stress is related to its elasticity, 23 and Claudio et al 24 found that Carotid endothelial shear stress reduction is an independent predictor of atherosclerosis. In addition, in a previous study, 25 increased TG levels and decreased HDL‐C levels were related to arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stretching can cause structural alteration of the arterial wall, including hyperplasia and hypertrophy of vascular smooth muscles, leading to arterial remodeling. Carotid tensile stress is related to its elasticity, 23 and Claudio et al 24 found that Carotid endothelial shear stress reduction is an independent predictor of atherosclerosis. In addition, in a previous study, 25 increased TG levels and decreased HDL‐C levels were related to arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement results show that SWD of the elderly group is lower than that of the young group, while CIMT and PWV are higher than that of the young group, which proves that SWD imaging has the potential to evaluate arterial viscoelasticity. Luo [53] studied the tensile stress changes (TS) of the carotid artery in two groups of healthy subjects of different ages under different viscoelasticity. They found that TS of the arterial wall was significantly associated with arterial viscoelasticity.…”
Section: Shear Wave Dispersion (Swd) Imagingmentioning
confidence: 99%
“…The arterial tree within the human body spans from the aorta, which is about 3 cm in diameter, down to small precapillary arteries of about 50 micrometers in diameter. While arterial wall has a heterogeneous structure composed of complex materials, its intrinsic stiffness is determined mainly by the proportion, arrangement and mechanical properties of elastic fibers [3,4], which change during aging and are subjected to the influence of various factors like hypertension, diabetes mellitus and lipidemia [5]. Increased arterial stiffness can appear prior to the development or manifestation of permanent vascular damage or cardiovascular disease.…”
Section: What Is Arterial Stiffness?mentioning
confidence: 99%
“…Moreover, the relationship between age and arterial stiffness is better captured by a nonlinear model rather than the traditional linear model approach [39]. One plausible explanation is that arterial walls exhibit viscoelastic biomechanical properties and display nonlinear stress-strain relationships that change complicatedly with age [3]. Chen et al [40] reported a J-shaped relationship between API and age, with the J-shaped curve displaying a complex pattern of change across age groups.…”
Section: Agementioning
confidence: 99%